X-ray scattering measurements of radiative heating and cooling dynamics. - Gregori, G; Glenzer, S; Fournier, K; Campbell, K; Dewald, E; Jones, O; Hammer, J; Hansen, S; Wallace, R; Landen, O (2008)
Spectrally and time-resolved x-ray scattering is used to extract the temperature and charge state evolution in a near solid density carbon foam driven by a supersonic soft x-ray heat wave. The measurements show a rapid heating of the foam material (approximately 200 eV/ns) followed by a similarly fast decline in the electron temperature as the foam cools. The results are compared to an analytic power balance model and to results from radiation-hydrodynamics simulations. Finally, the combination of charge state and temperature extracted from this known density isochorically heated plasma is used to distinguish between dense plasma ionization balance models.